Acute Disruption of the Dorsal Hippocampus Impairs the Encoding and Retrieval of Trace Fear Memories - Wilmot, Jacob H.; Puhger, Kyle; Wiltgen, Brian J. (Frontiers in Behavioral Neuroscience, 2019)
A major function of the hippocampus is to link discontiguous events in memory. This process can be studied in animals using Pavlovian trace conditioning, a procedure where the conditional stimulus (CS) and unconditional stimulus (US) are separated in time. While the majority of studies have found that trace conditioning requires the dorsal segment of the hippocampus, others have not. This variability could be due to the use of lesion and pharmacological techniques, which lack cell specificity and temporal precision. More recent studies using optogenetic tools find that trace fear acquisition is disrupted by decreases in dorsal CA1 activity while increases lead to learning enhancements. However, comparing these results is difficult given that some studies manipulated the activity of CA1 pyramidal neurons directly and others did so indirectly (e.g. stimulation of entorhinal cortex inputs). The goal of the current experiments, therefore, was to compare the effects of direct CA1 excitation and inhibition on the encoding and expression of trace fear memories. Our data indicates that stimulation of ArchT in dorsal CA1 pyramidal neurons reduces activity and impairs both the acquisition and retrieval of trace fear. Unlike previous work, direct stimulation of CA1 with ChR2 increases activity and produces deficits in trace fear learning and expression. We hypothesize that this is due to the artificial nature of optogenetic stimulation, which could disrupt processing throughout the hippocampus and in downstream structures.